ANALISIS ASESMEN SUMATIF AKHIR SEMESTER GENAP MATEMATIKA TERHADAP SELF-ESTEEM KELAS III SD NEGERI 2 MUDALREJO TAHUN AJARAN 2023/2024 - Amelia Wahyu Putri Wardani; Arum Ratnaningsih; Nurhidayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to determine the relationship between the results of the End-of-Semester Summative Assessment for the even semester of the Mathematics subject and the self-esteem of third-grade students at public alementary school 2 Mudalrejo for the 2023/2024 academic year. The background of the research arises from initial findings that there are variations in self-esteem among students, such as difficulties in socializing, a lack of courage in making decisions, and differing abilities in managing emotions, despite generally high Mathematics scores. These conditions prompted the researcher to examine whether academic achievement in the fundamentals of Mathematics is related to self-esteem. This research uses a quantitative approach with a simple correlational method. The research sample consisted of all third-grade students, totaling 26 respondents. Data were collected thru a Self-esteem questionnaire adapted from Coopersmith with 53 statement items and documentation of Mathematics report card grades. Data analysis techniques include descriptive statistics, normality tests, linearity tests, and Pearson correlation tests with the help of SPSS Statistics 26. The research results show that students' self-esteem scores range from 18 to 45, with an average of 33.58. Data shows that self-esteem is in the moderate category. The correlation test yielded a r value of 0.086 and a significance of 0.675. The significance value is greater than 0.05, so H0 is accepted. The data indicates that there is no significant relationship between Self-esteem and the ASAS results for the second semester in Mathematics. This indicates that self-esteem is not the main factor influencing academic achievement in the context of this study.